Exploiting Web Scraping for Education News Analysis Using Depth-First Search Algorithm - Arumi, Endah Ratna; Sukmasetya, Pristi (JOIN (Jurnal Online Informatika), 2020)
Online news is one source of data that is always up to date and provides information or factual data. The search engine is one of the features for users to be able to enter keywords based on the expected category quickly. The development of education in Indonesia makes it essential to discuss, in this study using unstructured data in online news with the keyword Education included as a parameter, and adding search methods in the field of Artificial Intelligence so that the data becomes more accurate. Data that used here was from online news, namely CNN Indonesia, Detikcom, and Liputan6. Using Python Programming with depth-first search method (DFS), when compared with the results data for relevant news. Web erosion using DFS will be very helpful in searching because this method can check the date data was sent and then track the destination URL. Of the three online media sites, Detikcom produces the highest monthly data yielding an average of 885 news about education. At the same time, Liputan6 has the least amount of data on average, 28 news per month, but the data obtained are very relevant compared to Detikcom and CNN Indonesia.